Students’ Perspectives Toward Grammar Teaching Methods in English Language Education Study Program - Fifi Novriana Suradin; Sri Widyarti Ali; Indri Wirahmi Bay (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of this research is to elucidate students' perspectives on grammar teaching methods. It observed 5th-semester students from the 2019 academic year, in English Language Education Study Program. Five students were chosen at random from each class, so the total sample for this study was 25. The descriptive quantitative research method was applied to this study. The information was gathered using a questionnaire that represented two grammar teaching methods: explicit and implicit. Each one consists of six statements, with several options for students to choose from, including strongly agree, agree, neutral, disagree, and strongly disagree. The findings revealed that each student has a different perspective on what method is required. The questionnaire results showed that approximately 80% of students agreed with every statement in the explicit method, and the majority of them chose neutral to the statements in the implicit method, with an average percentage of 37%-70%. As a result, students can be taught using both implicit and explicit methods, as both have advantages, and it is determined by the needs of each student.